The war for talent: the great business challenge (Dissertare, 2023)
For many companies, the attracting, selecting, training and retaining human talent process has become a real challenge. This article has, as a first objective, to identify the factors that explain the serious difficulties of companies globally related to attracting and hiring enough talented personnel to continue growing in their economic activities. The second objective aims to highlight the actions that an organization must necessarily carry out in order to retain talent. The third objective focuses on the description of some competencies, skills and talents that companies are currently looking for in order to avoid a setback in their objectives of growth and expansion of the commercial, technological, research or service activities that they provide. The methodological approach used in this article is qualitative, with a documentary design that is supported by an extensive review of the literature and a critical analysis of the researched material. Based on the approaches presented in this work in relation to the factors that explain the shortage of human talent, as well as the strategic approach to staff retention and the required skills, it is concluded that companies should carefully examine their internal standards, when as well as their policies for attracting, recruiting and retaining talent, while paying maximum attention to various aspects, such as the training of human talent, the recognition of performance, the application of emotional salary and the creation of a climate pleasant work.
Keywords: employer branding; human talent management; soft skills; talent retention; human talent